Technical Feasibility Assessment of Seaplane Operations at Tinabo Besar Island, Taka Bonerate National Park, Indonesia - Muhammad Fikram; Chairul Paotonan; Ashury Djamaluddin; Andi Mega Mustika (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
Taka Bonerate National Park (TBNP) is one of the largest marine conservation areas in Indonesia, renowned for its unique atoll ecosystem and high marine tourism potential. However, limited accessibility remains a major constraint for tourism development. This study aims to assess the technical feasibility of seaplane operations at Tinabo Besar Island as a potential waterbase. The research employed hydro-oceanographic analysis (wind, currents, waves, and bathymetry), measurement of aerial distance and travel time between Makassar and Tinabo, as well as a technical review of four seaplane types (Kodiak 100, Cessna 208 Caravan, Dornier Seastar, and DHC-6 Twin Otter). The results indicate that the hydro-oceanographic conditions around Tinabo Besar are predominantly safe for seaplane operations, with 90.34% of days in a year classified as suitable for flights, 7.31% as marginal, and 2.34% as critical. The lagoon bathymetry, ranging from –2 to > –40 m, supports safe water landings. The Makassar–Tinabo route, approximately 245 km, can be covered in 1.5–2 hours by seaplane, which is significantly more efficient compared to sea travel (12–15 hours). From a technical perspective, the Kodiak 100 and Cessna Caravan are considered the most efficient for regular operations, while the Twin Otter is more suitable for higher passenger demand. Thus, Tinabo Besar Island is deemed feasible as a seaplane operational site, although risk mitigation during the west monsoon and coral reef conservation efforts remain essential, given that the reef ecosystem is the main tourism attraction of Taka Bonerate National Park.